Pengaruh Variasi Penggunaan Perekat Tapioka Terhadap Kualitas Briket Limbah Padat Kotoran Sapi - Anasstasia, Titi Tiara; Yustiani, Fatma (Universitas Tanjungpura, 2025)
Livestock solid waste is the remaining waste from a livestock business activity which includes solid waste and liquid waste such as feces, urine and other waste. Continuous dumping of waste will cause environmental pollution. Processing cow dung waste into briquettes is one solution for landfilling solid waste at the Sidorejo Cattle Farm. The aim of this research is to determine the effect of variations in the amount of adhesive mixture on the quality of briquettes in terms of heating value parameters. The research method used in this research is divided into several stages, namely the purposive sampling method for taking cow dung samples, the experimental method, the laboratory test method, and the data analysis method using simple linear regression. Simple linear regression calculation to determine the effect of the amount of adhesive on the heating value and determine the predicted value. The amount of adhesive used in this study used 4 treatments with different variations in tapioca flour adhesive of 0 gr; 3 g; 5 gr; and 7 grams mixed with 300 grams of cow dung charcoal powder, this experiment was carried out 2 times. The final results showed the highest calorific value of 2,915 cal/g with a ratio of adhesive to charcoal powder of 7 grams: 300 grams, while the lowest calorific value was 2,234 cal/g with a ratio of adhesive to charcoal powder of 0 grams: 300 grams. The higher the number of adhesive variations, the calorific value produced will also increase